A compaixão como fundamento da moral em Schopenhauer - Dalcol, Mônica Saldanha (2014)
First of all, the following dissertation consists in a reconstruction and analysis of the major theoretical assumptions that led Schopenhauer to assert that human actions with moral value are only those derived from compassion for others. These assumptions are derived from his metaphysics of the will, a model of metaphysical characterization of the world and the human beings where the will assumes a key place, unseating optimistic visions of the human condition that conceptualizes the man as having power and autonomy. Against traditional ethical thought that believes that we act on our free will, Schopenhauer argues that we act according to our character and that is not built by our decisions throughout our lives, but it is simply revealed by them. The metaphysics of the Will, the present determinism in the doctrine of character and selfishness that rules the world as representation, arising from the principle of individuation, represent fundamental assumptions for the understanding of Schopenhauer's ethics developed in his major works on this topic: The World as Will and Representation and On the Basis of Morality. In second place, we present the main criticisms that Schopenhauer launches to Kantian ethics: first to the excessive Kantian formalism that separates morality from the actual experience of human beings, which, according to Schopenhauer, is precisely from where ethics should start. Subsequently, we will present Schopenhauer's criticism to the categorical imperative as an a priori law that imposes itself unconditionally. We will argue, thirdly, that from the metaphysical assumptions and criticisms against Kant, Schopenhauer comes to his own conception of compassion as the foundation of morals, where he will properly deal with the problem of explaining how an action is possible with genuine moral value amid the selfishness and one's incessant self-affirmation, which features our ordinary condition. Schopenhauer's answer consists, essentially, to say that the compassion is a kind of action entirely selfless, dedicated to the well-being of others. For these characteristics, compassion, as conceived by Schopenhauer, can not be taken as a simple human feeling, such as anger or joy, but its semantic core is defined as a closer model to an attitude of sympathy (a way of 'seeing the world in a correct perspective'), whose precise meaning can only be grasped from his metaphysics of the Will. Compassionate action involves a state of identification with the other, i. e., from the recognition of the unity of the Will, I am being able to identify that the suffering of others has the same configuration as my own suffering. Lastly, in the last chapter, we will present some criticisms and defenses of the proposed moral reasoning developed by Schopenhauer. A good portion of the criticism takes the assumption that compassion is a simple and foundational sense of morality. Against the criticism, for instance, our main argument is that the doctrine of Schopenhauer is not a kind of pure sentimentalism, but that compassion is more like a broader emotional attitude. We also aim to further analyze the latest perspectives for a moral theory centered on compassion from the analysis of Lawrence Blum's approach. From this analysis, we will see that,despite severe criticism, the path firstly opened by Schopenhauer has offered fruitful directions for contemporary moral-philosophical based reflections.